Investigation and Research on Yuanjia Village Tourism in Shaanxi Based on the Integrated Development of Agriculture and Tourism (Journal of Global Humanities and Social Sciences, 2024)
With the implementation of the national rural revitalization strategy, rural tourism development has become an important means of rural revitalization. And now people's living standards continue to improve, and people's demand for tourism has gradually changed from single to multiple. The new model of combining agriculture and tourism is constantly being sought after by people, and it is also better to drive the development of agriculture with tourism, thus promoting farmers' income. Yuanjia Village, as a typical representative of Shaanxi and even China's rural tourism development model, has a better research significance. For this reason, this paper chooses Yuanjia Village as the research object, focusing on the experience of tourists, to provide a reference for modeling Yuanjia Village tourism model.